KINEMASTER : CREATING ENGLISH LEARNING VIDEOS IN THE ERA OF DISRUPTION - Siskawati, Zulfia; Asmarika, Asmarika (Innovative: Journal Of Social Science Research, 2023)
This study examines the usage of the Kinemaster applications for creating English learning videos in elementary schools. The study used a descriptive-quantitative research design. The data was collected via a questionnaire. The findings revealed that: 1) 70% of respondents said they didn't know how to create a decent learning video. 2) Almost all respondents, approximately 76%, claimed that they were extremely familiar with the KineMaster application but did not understand how to utilize it. 3) 70% of respondents indicated they didn't know how to use the KineMaster software to create learning films. 4) Of the several challenges associated with creating learning films, 60% of respondents reported that developing learning content for the videos was extremely tough. 5) 85% of respondents felt that utilizing the Kinemaster tool made creating learning films easier. Keywords: KineMaster, learning videos, English.